2019
DOI: 10.9734/ajacr/2019/v3i130085
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Sorghum bicolor L. (Moench) and the Effectiveness of Some Organic Amendments in Remediation of Petroleum Oil-Vitiated Soils of an Automobile Repair Workshop in Urbanite Kampala

Abstract: Aims:To determine the potential of sweet sorghum (Epuripur 1995) and the effect of organic biostimulators: NPK fertilizer, cow dung and sewage sludge in remediation of petroleum oiladulterated soils from a garage in Kampala Metropolis, Uganda. Place and Duration of Study: The contaminated soils were obtained from New Katanga Boys automobile repair workshop in Wandegeya, Kampala, Uganda. Experiments were conducted Omara et al.; AJACR, 3(1): 1-10, 2019; Article no.AJACR.48785 2 between Methodology: 50 kg of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Our findings agree with Bartucca et al (2022) who also documented the ability of biostimulants to counteract the deleterious effects of pollutants on plants, thus increasing the phytoremediation efficiency of some species. Similar were the results by Omara et al (2019) on sweet sorghum. In addition, Fiorentino et al (2017) reported that biostimulated giant reed achieved higher shoot and root biomass, and accumulated significantly higher Zn amounts compared to the untreated plants.…”
Section: Resultssupporting
confidence: 88%
“…Our findings agree with Bartucca et al (2022) who also documented the ability of biostimulants to counteract the deleterious effects of pollutants on plants, thus increasing the phytoremediation efficiency of some species. Similar were the results by Omara et al (2019) on sweet sorghum. In addition, Fiorentino et al (2017) reported that biostimulated giant reed achieved higher shoot and root biomass, and accumulated significantly higher Zn amounts compared to the untreated plants.…”
Section: Resultssupporting
confidence: 88%
“…For this reason, remediation of such contaminated soils are still required to reduce the risk of exposure to the heavy metals by humans. Phytoremediation, one of the popular approaches used for this purpose utilizes higher plants and their associated rhizosphere microorganisms to remediate soils, sediments, surface and ground water contaminated with toxic metals, organics and radionuclides by either removing the pollutants or lowering their bioavailability [32][33][34]. Plants effect this using their roots in which the pollutants are accumulated, and thus their bioavailability can be modulated [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…In continuity of our environmental monitoring assessments [6][7][8][9][10][11][12][13], we report on the profile of water from Mpanga river which receives effluents from Kabundaire abattoir, Fort Portal, Uganda.…”
Section: Introductionmentioning
confidence: 99%